Language Variations Bapak Jokowi and Residents Interview in Responding to Damaged Roads in Lampung : Language Style - Alda Asriyani; Rosita Ambarwati (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
Language is very influential in life, because language is a communication tool used in everyday life, one of which is using language style. The purpose of this study was to find out the variety of languages used by Bapak Jokowi and the residents interviewed when working on damaged roads in Lampung. This study uses qualitative research, with data collection techniques using documentation. The results of the study found that there were differences in the variety of languages used by Bapak Jokowi and the residents in responding to the damaged roads in Lampung, there were 2 varieties of casual language; 3 consultative style; 2 formal styles; and 1 frozen style. And 4 casual style answers from local residents.